2015
DOI: 10.1001/jama.2015.3725
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Spores of NontoxigenicClostridium difficileStrain M3 for Prevention of RecurrentC difficileInfection

Abstract: IMPORTANCE Clostridium difficile is the most common cause of health care-associated infection in US hospitals. Recurrence occurs in 25% to 30% of patients. OBJECTIVE To determine the safety, fecal colonization, recurrence rate, and optimal dosing schedule of nontoxigenic C difficile strain M3 (VP20621; NTCD-M3) for prevention of recurrent C difficile infection (CDI). DESIGN, SETTING, AND PARTICIPANTS Phase 2, randomized, double-blind, placebo-controlled, dose-ranging study conducted from June 2011 to June 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
222
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(231 citation statements)
references
References 19 publications
3
222
3
3
Order By: Relevance
“…63 About two thirds (69%) of NTCD recipients were colonized, with only a 2% CDI recurrence rate in these patients.…”
Section: Non-toxigenic C Difficilementioning
confidence: 97%
“…63 About two thirds (69%) of NTCD recipients were colonized, with only a 2% CDI recurrence rate in these patients.…”
Section: Non-toxigenic C Difficilementioning
confidence: 97%
“…Recent randomized controlled studies have also shown that rates of these minor adverse effects were similar in treatment and control groups, suggesting that they are not necessarily intrinsic to the FMT material. 3,26 Currently, clinical trials that are approved by the FDA under an Investigational New Drug (IND) application are chiefly submitted as Phase I clinical trials and as their results are published, understanding of safety and attributable adverse effects of FMT will improve. Further, a national registry for FMT outcomes data was recently announced, which will also enhance short-and long-term safety end point data collection and feedback into appropriate donor selection and screening.…”
Section: Current Donor Selection and Screening Guidancementioning
confidence: 99%
“…26 Validated commercial assays testing alternative PCR targets that identify donors colonized with non-pathogenic strains of C. difficile, while ruling out asymptomatic carriage of other viral, bacterial and protozoal pathogens would be a helpful inclusion criterion for ideal stool donors. Understanding how to effectively screen donors will help to streamline logistical processes, while protecting the health of FMT recipients.…”
Section: Limitations Of Screening Asymptomatic Donorsmentioning
confidence: 99%
“…By contrast, patients asymptomatically colonized by non-toxigenic strains do not seem to have an increased risk or are even protected from progressing to CDI. This concept was recently tested in humans; patients who could be colonized by a non-toxigenic C. difficile strain after receiving standard of care treatment for CDI had significantly reduced CDI recurrence rates 187 . However, further explorations of this approach should consider that nontoxinogenic strains can become toxinogenic by horizontal gene transfer 188 , although it is unknown whether this process also occurs in a human host.…”
Section: Asymptomatic Carriagementioning
confidence: 99%